2021
DOI: 10.3389/fpsyt.2021.731348
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Stress Levels Associated With COVID-19 Pandemic of University Students in Turkey: A Year After the Pandemic

Abstract: The outbreak of COVID-19 has been affecting the daily lives of almost everyone and puts huge psychological pressure on people worldwide, including Turkey. Anxiety and stress levels among university students were already a public health concern. Our study aims to demonstrate the anxiety and stress levels of university students in Turkey after the outbreak of COVID-19 according to the Coronavirus Anxiety Scale (CAS) and COVID Stress Scale (CSS). CAS is a brief mental health screener to identify probable cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 45 publications
1
11
1
Order By: Relevance
“…Regarding health stressors, COVID-19 and feelings of isolation due to the infection were clear. In a study from Turkey, it was observed that the danger of infection was the highest stressor among university students assessed during the pandemic [ 69 ]. Although our study did not rate the economic, educational and health stressors for students, feelings of isolation due to the pandemic correlated with higher levels of depression, anxiety, and stress in the DASS-21 scale, making that a major health stressor that needs to be addressed, should mental health support be given to students.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding health stressors, COVID-19 and feelings of isolation due to the infection were clear. In a study from Turkey, it was observed that the danger of infection was the highest stressor among university students assessed during the pandemic [ 69 ]. Although our study did not rate the economic, educational and health stressors for students, feelings of isolation due to the pandemic correlated with higher levels of depression, anxiety, and stress in the DASS-21 scale, making that a major health stressor that needs to be addressed, should mental health support be given to students.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there has been an increase in problematic internet use among nursing students during the pandemic period (Cai et al, 2021 ; Shehata & Abdeldaim, 2021 ). Many studies are showing that anxiety levels and social media addictions increased in university students during the pandemic period in Turkey (Durbas et al, 2021 ; Örgev & Kınalı, 2022 ; Parlak Sert & Başkale, 2022 ). In a study conducted on health sciences students during the pandemic period, health anxiety and cyberchondria levels were found to be higher in those who have not had COVID-19 before (Kurcer et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous people have lost a loved one due to COVID-19 and have lived with the fear that such a tragedy might reoccur. Such experiences and the uncertainty caused by the pandemic create great stress and anxiety [6]. Additionally, poor sleep quality has been reported globally with an increase in sleep disturbances, along with a concomitant dependence on sleep medication [7].…”
Section: Introductionmentioning
confidence: 99%